2023
DOI: 10.1093/jjco/hyad037
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural comparison of continuous deep sedation for advanced cancer patients in East Asian countries: prospective cohort study

Abstract: Objective Cultural, social, and legal factors have been known to affect physicians’ practice of continuous deep sedation. There have been few quantitative studies to compare continuous deep sedation practice in Asian countries. We aimed to describe and compare clinical characteristics of continuous deep sedation in Japan, Korea and Taiwan. Methods Patients with advanced cancer admitted to participating palliative care units w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“… 24 A similar study in Switzerland showed that 24.5% of all patients with non-sudden deaths received PS, with a higher prevalence for patients dying in PCUs. 25 Rates of continuous deep sedation at PCUs in East Asian countries have been reported as 10% in Japan, 16% in Korean, and 22% in Taiwan, 26 whereas Brazilian acute care settings have an estimated prevalence of 54.2%. 27 …”
Section: Discussionmentioning
confidence: 99%
“… 24 A similar study in Switzerland showed that 24.5% of all patients with non-sudden deaths received PS, with a higher prevalence for patients dying in PCUs. 25 Rates of continuous deep sedation at PCUs in East Asian countries have been reported as 10% in Japan, 16% in Korean, and 22% in Taiwan, 26 whereas Brazilian acute care settings have an estimated prevalence of 54.2%. 27 …”
Section: Discussionmentioning
confidence: 99%